Detection of Genes Encoding of Extended-Spectrum and AmpC β-Lactamases in Klebsiella pneumoniae Isolates from Clinical Specimens - Abdulhasan, Ghusoon A; Fadhil, Hula Y; Jasem, Kifah A (Al-Nahrain Journal of Science, 2018)
Klebsiella pneumoniae is an important pathogen of nosocomial infections and has rapidly become the most common producing beta lactamases that resistance for many antimicrobial agents. Thus, our study aimed to identify K. pneumoniae isolates harboring SHV, TEM, CTX-M and AmpC β-lactamase genes and the relation between them and with some antimicrobial resistance to avoid treatment failure. Sensitivity disc test and PCR technique were done on 24 clinical isolates of K. pneumoniae. The PCR results showed that blaSHV, blaTEM, blaCTX-M and blaAmpC genes were present in 91.67% of the isolates. Significance appearance of resistance genes was 75% for each blaSHV and blaCTX-M, 62.5% for blaTEM, while blaAmpC in 16.7%. Finding pointed out that blaAmpC gene present with highly significant in bacterial isolates which lacking the blaSHV and blaCTX-M. Moreover, blaSHV and blaTEM occurred on significant correlation with blaCTX-M. Antimicrobial discs (CTX, CDZ, CRO and CL) correlating with resistance genes (blaCTX-M, blaSHV and blaTEM). Remarkably, 41.67% of bacterial isolates have three of cephalosporine β-lactamase genes due to the common used of cephalosporine third generation for treatment.